2022
DOI: 10.3390/ma15103564
|View full text |Cite
|
Sign up to set email alerts
|

Modification of CeNi0.9Zr0.1O3 Perovskite Catalyst by Partially Substituting Yttrium with Zirconia in Dry Reforming of Methane

Abstract: Methane Dry Reforming is one of the means of producing syngas. CeNi0.9Zr0.1O3 catalyst and its modification with yttrium were investigated for CO2 reforming of methane. The experiment was performed at 800 °C to examine the effect of yttrium loading on catalyst activity, stability, and H2/CO ratio. The catalyst activity increased with an increase in yttrium loading with CeNi0.9Zr0.01Y0.09O3 catalyst demonstrating the best activity with CH4 conversion >85% and CO2 conversion >90% while the stability increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…57,58 0.07, and 0.09); weight loss increases. The same trend is observed in CeNi 0.9 Zr 0.1−x Y x O 3 (x = 0.00, 0.05, 0.07, and 0.09) catalyst system by Lanre et al 49 The transmission electron microscope image of La 0.6 Ce 0.4 Ni 0.9 Zr 0.01 Y 0.09 O 3 catalyst (fresh and spent) and corresponding average Ni particle size distribution are shown in Figure 5B,C(b,c). Significant filamentous coke formation is observed over the spent La 0.6 Ce 0.4 Ni 0.9 Zr 0.01 Y 0.09 O 3 catalyst.…”
Section: Catalyst Characterization Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…57,58 0.07, and 0.09); weight loss increases. The same trend is observed in CeNi 0.9 Zr 0.1−x Y x O 3 (x = 0.00, 0.05, 0.07, and 0.09) catalyst system by Lanre et al 49 The transmission electron microscope image of La 0.6 Ce 0.4 Ni 0.9 Zr 0.01 Y 0.09 O 3 catalyst (fresh and spent) and corresponding average Ni particle size distribution are shown in Figure 5B,C(b,c). Significant filamentous coke formation is observed over the spent La 0.6 Ce 0.4 Ni 0.9 Zr 0.01 Y 0.09 O 3 catalyst.…”
Section: Catalyst Characterization Resultssupporting
confidence: 81%
“…In the CeNi 0.9 Zr 0.1−x (x = 0, 0.03, 0.05, and 0.07) catalyst system, Lanre et al demonstrated the absence of perovskite phase, presence of individual metal oxide phases, and the presence of mixed yttrium cerium oxide. 49 Dezvareh et al showed that on substitution La by 0.1% Ce at the A site and Ni by 0.2% Zr at the B site, metal support interaction increased, resulting in increased activity. 40 The synergic effect of two metal oxides (ceria-lanthana) on redox and basicity function was previously utilized in the catalytic combustion of methane 50 and oxidation of CO. 51 Overall, "CH 4 decomposition over Ni," "strong interaction of CO 2 with lanthanum," "redox cycle and CO 2 activation with ceria," and "instant lattice oxygen availability by Zr and Y" are some catalyst merits in favor of DRM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CsNi 0.9 Zr 0.1 O 3 catalyst displayed CH 4 conversion >70%, CO 2 conversion >80%, and H 2 /CO >0.90, while the LaNi 0.9 Zr 0.1 O 3 catalyst displayed CH 4 conversion >65%, CO 2 conversion >75%, and H 2 /CO >0.90 for the DRM reaction performed at 1073 K for 7 hours' time on stream. CeO 2 modifies the catalytic features of nickel-based catalysts in DRM based on its redox features and enables it to support CO 2 activation (Ce 2 O 3 + CO 2 → 2CeO 2 + CO) [42,43]. The value of the H 2 /CO ratio theoretically equals one but side reactions in the DRM experiment influence its actual value.…”
Section: Catalyst Activitymentioning
confidence: 99%
“…21 Alkaline earth metals are known to function as catalytic promoters that improve the stability of the catalyst by suppressing carbon deposition. 22 Specifically, the doping of alkaline earth metals improves the reducibility of perovskite-type perovskites and generates more active sites, thus improving the catalyst activity. Additionally, the surface oxygen species generated by the doping of alkaline earth metals significantly improve the ability of La 2 O 3 to both adsorb and desorb oxygen.…”
Section: Introductionmentioning
confidence: 99%